Zustand und Entwicklung wirtschaftlich wichtiger Grundfischbestände im Nordost-Atlantik - Schöne, Rüdiger (1995)
A review of the NE Atlantic stocks of cod, haddock, saithe, redfish and Greenland halibut is given. The results are based on the assessments of the ICES "Arctic Fisheries Working Group" and the critical examination of the ICES "Advisory Committee on Fisheries Managment (ACFM)". Johann Heinrich von Thünen-Institut, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery research in 2010